Secret pizza party - Rubin, Adam, 1983-; Salmieri, Daniel, 1983- (New York : Dial Books for Young Readers, 2013)
While Raccoon is eating pizza at his secret pizza party, he sees a masquerade party going on in the house next door to him and joins the fun.
Keywords: Raccoon -- Fiction; Parties -- Fiction; Pizza -- Fiction; Secrets -- Fiction; Humorous stories; Raccoon -- Juvenile fiction; Parties -- Juvenile fiction; Pizza -- Juvenile fiction; Secrecy -- Juvenile fiction; Humorous stories